delta-Tocopherol prevents methylglyoxal-induced apoptosis by reducing ROS generation and inhibiting apoptotic signaling cascades in human umbilical vein endothelial cells - Do, Moon Ho; Kim, Su Nam; Seo, Seung-Yong; Yeo, Eui-Ju; Kim, Sun Yeou (ROYAL SOC CHEMISTRY, 2015)
Methylglyoxal (MGO) is a highly reactive metabolite of glucose, which is known to cause damage and induce apoptosis in endothelial cells. Endothelial cell damage is implicated in the progression of diabetes-associated complications and atherosclerosis. Nuts are high in vitamin E. Consumption of nuts has been recommended for the prevention of cardiovascular disease. However, different nuts contain different forms of vitamin E, which can have different effects on endothelial cells. In this work, we investigated the protective effect of different isoforms of vitamin E on MGO-induced apoptosis in human umbilical vein endothelial cells (HUVECs). Among all forms of vitamin E, delta-tocopherol showed the highest effect on apoptosis of HUVECs. We also compared the anti-apoptotic activity of delta-tocopherol with that of alpha-tocopherol in MGO-treated HUVECs. Pretreatment with alpha-or delta-tocopherol significantly inhibited MGO-induced changes in cell morphology, cell death, and production of intracellular reactive oxygen species. delta-Tocopherol prevented MGO-induced apoptosis in HUVECs by increasing Bcl-2 expression and decreasing Bax expression. Interestingly, alpha-tocopherol also inhibited these factors but to a lesser extent than delta-tocopherol. MGO was found to activate mitogen-activated protein kinases (MAPKs). Compared to pretreatment with alpha-tocopherol, pretreatment with delta-tocopherol more strongly inhibited the activation of MAPKs, such as JNK and ERK1/2. These findings suggest that delta-tocopherol may be a more effective regulator of MGO-induced apoptosis than alpha-tocopherol.
Keywords: GLYCATION END-PRODUCTS; ENDOPLASMIC-RETICULUM STRESS; VITAMIN-E; CARDIOVASCULAR-DISEASE; GAMMA-TOCOPHEROL; ALPHA-TOCOPHEROL; IN-VIVO; ANTIINFLAMMATORY ACTIVITIES; CORDYCEPS-MILITARIS; CANCER CELLS